L’eclatement De La Distribution Des Produits D’assurances Au Maroc Quel Avenir Pour La Présentation Des Opérations D’assurances ? - Rahal, Hicham (European Scientific Journal, ESJ, 2017)
The primary purpose of this article is to present a legal research on the evolution of the distribution of the insurance sector in Morocco. This aims to provide an overview on the current trend in the retail insurance market and anticipate future challenges faced by the traditional insurance distributors with the current legal system. This article consists of four main parts: 1) stape of legal framework and organization of the Moroccan insurance market; 2) opening stage of the Moroccan insurance market to new players; 3) the consequences and risks of opening of the Moroccan insurance market; and 4) Conclusion.